Alternatives to islet transplantation: future cell sources of beta-like cells - Bruns, Helge; Schultze, Daniel; Schemmer, Peter (Clinical transplantation, 2013)
Cell transplantation is a treatment option for diabetes, metabolic liver disease in children, and leukemia. Except for the latter indication, solid organ transplantation is one of the available therapies but can be replaced by cell transplantation. However, due to the limited amount of cells that can be transplanted and due to rejection, results of cell transplants are still inferior to solid organ transplantation; there is a general shortage of donor organs, and cell isolation is limited to organs which cannot be transplanted as a whole for anatomic reasons. Therefore, alternatives to islets and beta cells are needed. There are some cells which can be generated from the recipient and would not be rejected; still, immunosuppression would be required to prevent reoccurrence of type I diabetes unless durable tolerance to beta cells could be induced. Generating beta cells for transplant from the recipient would help to overcome the lack of available organs. Moreover, understanding the underlying mechanisms of differentiation of these cells into beta-like cells would deepen our understanding of both pathophysiology and development of diabetes mellitus type I. This article examines embryonal stem cells, induced pluripotent cells, mesenchymal stromal cells, and hepatocytes as potential alternatives to beta-cell transplantation.